“Analisa Konfigurasi Hubungan Primer Dan Sekunder Transformator 3 Fasa 380/24 V Terhadap Beban Non Linier” - Mohd Yogi Yusuf; Firdaus Firdaus; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The use of non-linear loads are increasingly widespread. The non-linear load can cause distortion of the voltage wave and current wave. This waveform distortion commonly called harmonics. The problems that can be caused by harmonics include increased energy losses, overheating and low work factor. In practice the presence of harmonics is carrying losses on a variety of tools, one of which is the distribution transformer. In this research designed to determine the harmonic simulation in every winding connection. Software used in this research was ETAP 11.0. Results from this research indicate a winding connection most good to be used in transformer based on the value of THD.Keywords: Harmonic current, Transformer, THD, ETAP, Winding Connection